2014
DOI: 10.3390/ijms151017622
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Root-Related Transcription Factors Associated with Flooding Tolerance of Soybean (Glycine max)

Abstract: Much research has been conducted on the changes in gene expression of the model plant Arabidopsis to low-oxygen stress. Flooding results in a low oxygen environment in the root zone. However, there is ample evidence that tolerance to soil flooding is more than tolerance to low oxygen alone. In this study, we investigated the physiological response and differential expression of root-related transcription factors (TFs) associated with the tolerance of soybean plants to soil flooding. Differential responses of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 80 publications
1
65
0
2
Order By: Relevance
“…As the restriction enzymes used in developing SoySNP50K array might have cleaved the genomic position that harbour this LRN gene. The first nonsynonymous SNP (Mut 1) that alters amino acid from serine to alanine was detected in 15 elite soybean accessions of Germplasm Pool II, which includes PI 416937 and PI 408105A known to produce high LRNs and perform better under drought (Pantalone, Burton, & Carter, ) and flooding (Valliyodan et al, ) stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the restriction enzymes used in developing SoySNP50K array might have cleaved the genomic position that harbour this LRN gene. The first nonsynonymous SNP (Mut 1) that alters amino acid from serine to alanine was detected in 15 elite soybean accessions of Germplasm Pool II, which includes PI 416937 and PI 408105A known to produce high LRNs and perform better under drought (Pantalone, Burton, & Carter, ) and flooding (Valliyodan et al, ) stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The natural genetic variation in root traits is a largely untapped resource that has had limited use as selection criteria in crop breeding programs (Lynch & Brown, ; York, Nord, & Lynch, ). Soybean plant introductions (PIs) 416937 (King, Purcell, & Brye, ; Prince, Song, et al, ; Prince, Murphy, et al, ) and 408105A (Valliyodan et al, ) were shown to exhibit profuse fibrous root systems, but no genes controlling the observed morphological variations were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Roots directly face damage during waterlogging stress due to cellular anoxia, with root meristems showing particular vulnerability (Kozlowski, ; Valliyodan et al, ; Valliyodan et al, ). Damaged root system fails in water and nutrient uptake, especially after waterlogging (soil drying; Kramer & Jackson, ).…”
Section: Disscusionsmentioning
confidence: 99%
“…Root growth and morphology under waterlogging and the resulting hypoxia during these early stages have been verified in soil and hydroponic cultivation systems. In soil cultivation, root dry weight (RDW) had decreased significantly by 7 days of waterlogging at the V1 stage (Sallam & Scott, 1987;Valliyodan et al, 2014;Yamane & Iijima, 2016). Although genetic variation in the response to waterlogging at the flowering stage was observed in various soybean cultivars (Rhine et al, 2010;VanToai et al, 1994VanToai et al, , 2010, few researchers have screened cultivars by root morphology under waterlogging during the early vegetative stage.…”
Section: Experiments 1: Evaluation Of Hypoxia Tolerance Of Soybean In mentioning
confidence: 99%